Immunity peculiarities of neonates in case of perinatal pathology - О. S. Godovanets; A. B. Mihalchan; O. I. Godovanets; V. V. Bezruk; T. O. Bezruk (Zaporožskij Medicinskij Žurnal)
The immune system as one of the regulating systems of the body determined peculiarities of child adaptation after birth stipulating physiology of adaptation or perinatal pathology formation. Objective: to study peculiarities of immunological indices in case of neonates’ perinatal pathology to detect their role in pathogenesis and formation of diseases severity. Materials and methods. The group of term infants with clinical signs of perinatal pathology (173 individuals) was examined. They were divided into two groups: group A included those with diagnosed severe forms of diseases (121 individuals), and group B included 52 infants with general moderate severity of perinatal pathology. The group of comparison included 82 newborns without substantial adaptive deviations after birth. IL1 and IL6 levels were examined by means of immunofluorescence method “Clonospectr” using the reagents produced by “ProCon”. Absolute and relative amount of СD2+-associated Т and NK-lymphocytes, СD14+-associated monocytes, СD15+-associated neutrophils, СD19+-associated В-lymphocytes and СD54+-associated ІСАМ-1 cells were determined by means of immunofluorescence method “Status” using the set of monoclonal and polyclonal antibodies produced by “Sorbent”. The data obtained were statistically processed with the application of applied programs package used for medical-biological studies “Statgraphics Centurion XVI.I” [2011] on the personal computer Pentium MMX CPU. Results. The results obtained were indicative of considerable changes in the immune system indices in newborns under conditions of birth stress and hypoxia. It has been found that a term newborn has a special different from that of adults biologically mediated state of immune system, that can determine both the development of physiological adaptation and under certain circumstances excessive reactions of systemic inflammation, autoimmune processes and destruction of tissues. One of the evidences of immune system components participation in perinatal pathology pathogenesis is detected correlation between immune disorders severity and clinical manifestation of diseases, as well as immune indices normalization in a long-term organism adaptation formation. Conclusions. Based on the data obtained it has been concluded that immune system status determination is reasonable for diagnostics of disadaptation syndrome severity in early neonatal period.